Enzyme Replacement Therapy in CLN2-Associated Retinopathy - Priglinger, Claudia; Courage, Carolina; Maier, Esther M. (Klinische Monatsblätter für Augenheilkunde, 2025)
Neuronal ceroid lipofuscinoses, also known as Batten disease, are comprised of a group of genetically heterogenous neurodegenerative conditions, characterized by dementia, epilepsy, motor deterioration, and blindness. The underlying pathology is a dysregulation of lysosomal catabolic protein metabolism, resulting in an accumulation of lipofuscein-like material within the lysosomes in neuronal tissue, which ultimately leads to atrophy in the central nervous system and in the retina. Ceroid lipofuscinosis type 2 (CLN2) is caused by biallelic pathogenic variants in the TPP1 gene, encoding lysosomal tripeptidyl peptidase 1 (TPP-1). The classic late-infantile phenotype of CLN2 disease has an age of onset between 2 and 4 years and manifests with seizures and speech delay, followed by progressive cognitive and motor decline, vision loss, and early death. Vision loss occurs secondary to retinal degeneration and begins in the perifoveal ellipsoid zone, leading to bullʼs eye maculopathy, followed by generalized retinal thinning. In 2017, an intracerebroventricular enzyme replacement therapy (ERT) using recombinant human TPP1 (rhTPP1), cerliponase alfa, was approved as a disease-modifying treatment for CLN2 disease. The therapy slows psychomotor decline but fails to prevent loss of vision. In a canine model of CLN2 disease, intravitreal rhTPP1 was shown to halt retinal degeneration. A prospective, interventional, controlled, open-label compassionate-use study evidenced safety of 0.2 mg intravitreal rhTPP1 every 8 weeks in humans and its efficacy in reducing the rate of macular volume loss in patients who were still in the degenerative phase. One ongoing clinical phase I/II study is investigating the safety and efficacy of intravitreal rhTPP1 at 4 weekly intervals over 24 months (NCT05152914); another clinical phase II dose escalation trial is planned. In this review, we summarize the current knowledge on ERT for CLN2 retinopathy, complemented with our own experience from an individual treatment. The treatment now appears to be safe and markedly delays retinal degeneration, thereby preserving visual function and increasing the quality of life of the patient. This could be particularly relevant for those patients who were started on intracerebroventricular ERT early and still have good motor and language function. For this patient population, intravitreal ERT could be a valuable bridging therapy until other therapies such as gene therapy become available.
Keywords: genetics; pediatric ophthalmology; retina